Strategy to Increase Student Interest through Service Quality, Promotion, and Islamic Education Fees - Kartiko, Ari; Rohmania, Nur Richa (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Student interest in school selection is shaped by various factors, including educational quality, facilities, tuition fees, location, institutional reputation, personal preferences, and parental support. This study aims to examine the influence of service quality, promotion, and educational costs on students’ interest in choosing a school. Employing a quantitative approach, data were collected through questionnaires distributed to 72 respondents and analyzed using SPSS version 24. The results indicate that service quality (X1) and educational costs (X3) do not significantly influence student interest (Y), as evidenced by T-count values of 0.573 and 0.027, both below the T-table threshold of 1.995. Conversely, promotion (X2) demonstrates a significant positive effect on student interest, with a T-count of 2.349 and a significance value of 0.022. The F-test results reveal that, collectively, the three variables do not exert a simultaneous influence on student interest (F-count = 2.532 < F-table = 3.12; p = 0.064 > 0.05). The novelty of this research lies in its identification of promotion as the primary factor influencing student enrollment decisions, despite the commonly assumed importance of service quality and costs. These findings offer practical implications for educational institutions, particularly Islamic schools, in designing targeted and effective marketing strategies to enhance student recruitment.